An exploration of makeup and all its possibilities through the lived and learned experiences of upper/middle class women in Dhaka - Mohsin, Mehnaz (Brac University, 2023)
This thesis is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Social Sciences in Economics, 2022.